2018
DOI: 10.18092/ulikidince.444201
|View full text |Cite
|
Sign up to set email alerts
|

Tasarruflar Ve Makroekonomi̇k Deği̇şkenler Arasindaki̇ Uzun Dönemli̇ İli̇şki̇: Oecd Ülkeleri̇ Örneği̇

Abstract: Ülke ekonomilerinin belirlenen iktisadi hedeflere erişmesinde, üretken yatırımlar ve bu yatırımların finansmanı kritiktir. Bu yönüyle tasarruflar yatırımların lokomotifi olarak değerlendirilebilir. Tasarrufların bu misyonu göz önünde bulundurulduğunda, belirleyicilerinin neler olduğu dikkat çekicidir. Bu çerçevede, çalışmanın amacı 2006-2015 döneminde 21 OECD ülkesi için tasarruf türlerine göre makroekonomik değişkenlerin etkilerinin Ortalama Grup Dinamik En Küçük Kareler (DOLSMG) panel eş bütünleşme yöntemiyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Callen and Thimann (1997), in their study on 21 OECD countries, concluded that growth, demographic changes, inflation, real interest rate and unemployment rate play important roles for private and government savings. Bulut and Karakaya (2018) also investigated the relationship between savings and macroeconomic variables. According to the estimation results, it is seen that the variables of income per capita, short-term real interest rate and inflation have a negative effect on private savings, while liquidity has a positive effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Callen and Thimann (1997), in their study on 21 OECD countries, concluded that growth, demographic changes, inflation, real interest rate and unemployment rate play important roles for private and government savings. Bulut and Karakaya (2018) also investigated the relationship between savings and macroeconomic variables. According to the estimation results, it is seen that the variables of income per capita, short-term real interest rate and inflation have a negative effect on private savings, while liquidity has a positive effect.…”
Section: Literature Reviewmentioning
confidence: 99%